2021
DOI: 10.1016/j.jisa.2021.102940
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Software Defined Network to secure communications in a swarm of drones

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…C. Guerber et al propose an SDN solution for external threats and an RF classifier-based ML solution for intra-network attacks. As a result, they observed that the proposed system was successful in detecting abnormal behavior [13].…”
Section: A Trust Managementmentioning
confidence: 89%
“…C. Guerber et al propose an SDN solution for external threats and an RF classifier-based ML solution for intra-network attacks. As a result, they observed that the proposed system was successful in detecting abnormal behavior [13].…”
Section: A Trust Managementmentioning
confidence: 89%
“…• Securing Communications in a Swarm of Drones: Another innovative application involved machine learning in conjunction with Software Defined Network (SDN) technologies to bolster the security of communication networks within drone swarms. The implemented solution employed a Random Forest Classifier-based machine learning model to detect prevalent network attacks, including denial of service, port scanning, and brute force attacks, showcasing the versatility of machine learning in diverse network scenarios [21].…”
Section: Machine Learning In Network Securitymentioning
confidence: 99%
“…How do ML techniques improve the performance of Flying Ad Hoc Network? Since ML techniques have been broadly employed in wireless networks, especially in FANETs of autonomous UAVs to train network nodes to control, monitor, and predict different communication parameters, such as traffic patterns, node positioning, the behavior of wireless channels, and so forth (Guerber et al, 2021;Oliveira et al, 2021), an opportunity was identified to propose this SLR covering this subject domain. However, as this subject is complex, other side topics needed to be included to make the SLR more useful and comprehensive.…”
Section: Research Questions Raised In This Slrmentioning
confidence: 99%